Postoperative Rigid Cervical Collar Leads to Less Axial Neck Pain in the Early Stage After Open-Door Laminoplasty—A Single-Blinded Randomized Controlled Trial. Issue 3 (3rd August 2018) - Cheung, Jason Pui Yin; Cheung, Prudence Wing Hang; Law, Karlen; Borse, Vishal; Lau, Yuk Ming; Mak, Ling Fung; Cheng, Aldous; Samartzis, Dino; Cheung, Kenneth Man Chee
Abstract: BACKGROUND: Cervical collars are used after laminoplasty to protect the hinge opening, reduce risks of hinge fractures, and avoid spring-back phenomena. However, their use may lead to reduced range of motion and worse neck pain. OBJECTIVE: To investigate the clinical, radiological, and functional outcomes of patients undergoing single-door laminoplasty with or without collar immobilization. METHODS: This was a prospective, parallel, single-blinded randomized controlled trial. Patients underwent standardized single-door laminoplasty with mini-plates for cervical myelopathy and were randomly allocated into 2 groups based on the use of collar postoperatively. Clinical assessments included cervical range of motion, axial neck pain (VAS [visual analogue scale]), and objective scores (short-form 36-item, neck disability index, and modified Japanese Orthopaedic Association). All assessments were performed preoperatively and at postoperative 1, 2, 3, and 6 wk, and 3, 6, and 12 mo. Comparative analysis was performed via analysis of variance adjusted by baseline scores, sex, and age as covariates. RESULTS: A total of 35 patients were recruited and randomized to collar use (n = 16) and without (n = 19). There were no dropouts or complications. There were no differences between groups at baseline. Subjects had comparable objective scores and range of motion at postoperative time-points. Patients without collar use had higher VAS at postoperative 1 wk (5.4 vs 3.5; P = .038) and 2 wk (3.5 vs 1.5; P = .028) but subsequently follow-up revealed no differences between the 2 groups. CONCLUSION: The use of a rigid collar after laminoplasty leads to less axial neck pain in the first 2 wk after surgery. However, there is no additional benefit with regards to range of motion, quality of life, and complication risk.